Adapting Sufi Spiritual Forms to Promote Christian Spiritual Growth - Abraham, Nicole (Mission studies, 2017)
Sufis took Islam to many parts of Asia and in some of those countries still continue to have a significant impact. Using Kraft’s model of dynamic equivalence this paper examines the Sufi spiritual forms of dhikr and samaʾ. Taking his parameters of form, function and meaning, these forms have been researched in terms of their use in fostering the Christian spiritual growth of Muslim seekers/followers of Jesus Christ in one of those Asian contexts. The assessment seeks to discover the degree to which they are compatible or may create difficulties with similar Christian forms. Following a brief overview of Sufism, the dhikr is considered in terms of its form, function and meaning. Both the fikr, the complement of the dhikr and the samaʾ are examined briefly. Then, the main issues highlighted are examined from a Christian theological perspective. Following Hiebert, a brief consideration is also given in terms of Christian history and traditions. Finally, observations are made as to how compatible these forms are within the Christian context while also outlining some of the possible problems.